MEDAN MAKNA MENANGKAP HASIL LAUT DALAM BAHASA MELAYU DIALEK PONTIANAK DI SUNGAI KAKAP - Masita, Siti; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractCatching the seafood is the activity of fishermen to hunt for fish and other sea products. This research related to linguistic focus on the study of the meaning field of catching sea product in the Malay dialect of Pontianak on the Sungai Kakap. This research uses the descriptive method with qualitative research form. The instruments used are leksem, vocabularies of the tools, part of tools, techniques, and products obtained. The researcher conducted the data analysis of the meaning component, the lexical meanings and the semantic function based on the classification of the tools, part of the tools, techniques, and the obtained seafood. From this research, it found leksem contained in catching of sea products in totals 98 leksem consisting of 5 leksem fishing gears, 16 catching phrases, 14 leksem part tools, 15 phrase tool parts, 14 technicals leksem, 4 leksem kinds of seafood, 30 phrase seafood . The data was obtained from the interview conducted by researcher during research in Kakap Village and Sungai Kupah Village, Sungai Kakap District, Kubu Raya Regency.Keywords: Catching seafood, Malay dialect of Pontianak, component of meaning, meaning of lexical, semantic function